English for Da'wah? L2 motivation in Indonesian pesantren schools. (November 2020) - Farid, Achmad; Lamb, Martin
Abstract: Anecdotal evidence suggests that some students, in some of Indonesia's Islamic boarding schools (pesantren), harbor negative attitudes towards English, prompting resistance to learning the language at individual and institutional levels. This paper reports on an empirical study investigating this issue in three pesantren in Java. Employing Dörnyei's (2005) L2 Motivational Self System as the main theoretical framework, a questionnaire consisting of well-established and context-specific constructs was designed to measure students' motivation for learning English (n = 376). The one-way MANOVA performed suggested that religious factors do play a role in shaping learners' motivation. To further examine this, a follow-up qualitative study involving class observations and student interviews was conducted. This revealed that the participants relate their motivation to their spiritual vision, i.e. using English mainly as a means of da'wah (Islamic propagation) and for communicating with other Muslims worldwide. However, this da'wah motive does not appear to generate much learning effort, and is possibly a way of overcoming the dissonance they feel in studying the non-believer language. The paper concludes by emphasizing the need for L2 researchers to further examine religious attitudes and religiosity as consequential socio-cultural aspects of learning English with pedagogical implications for institutions in many global contexts.